2017
DOI: 10.1186/s13287-017-0708-x
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid phenethyl ester promotes haematopoietic stem/progenitor cell homing and engraftment

Abstract: BackgroundSeveral studies have suggested that caffeic acid phenethyl ester (CAPE) can induce the expression of hypoxia inducible factor-1α (HIF-1α) protein. We determined whether CAPE has a novel function in improving the homing and engraftment of haematopoietic stem/progenitor cells (HSPCs) by regulating HIF-1α gene expression in the bone marrow (BM) niche.MethodsFor survival experiments, lethally irradiated C57BL/6 mice were injected with a low number of BM mononuclear cells (MNCs) and CAPE according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…HIF-1α is stabilized in HSCs and regulates HSC activity/quiescence 131, 132 . Pharmacological increases in HIF-1α promote HSC homing and engraftment also by upregulating surface CXCR4 expression 133 . CXCR4 expression upregulation results from HIF-1α binding with hypoxia response elements, located at –1.3 kb from the transcription start site of the CXCR4 promoter region.…”
Section: Improving Hematopoietic Stem Cell Homing To Enhance Cord Blomentioning
confidence: 99%
“…HIF-1α is stabilized in HSCs and regulates HSC activity/quiescence 131, 132 . Pharmacological increases in HIF-1α promote HSC homing and engraftment also by upregulating surface CXCR4 expression 133 . CXCR4 expression upregulation results from HIF-1α binding with hypoxia response elements, located at –1.3 kb from the transcription start site of the CXCR4 promoter region.…”
Section: Improving Hematopoietic Stem Cell Homing To Enhance Cord Blomentioning
confidence: 99%
“…Furthermore, it was demonstrated that HIF-1α is required for dmPGE2 mediated CXCR4 upregulation, enhanced HSC migration and homing. Recent work from another group reported that caffeic acid phenethyl ester (CAPE) administration promotes HSC homing and engraftment by inducing expression of HIF-1α [45]. CAPE treatment upregulated protein levels of HIF-1α and CXCL12 in BM endothelial cells.…”
Section: Stabilization Of Hif-1α Promotes Hsc Homingmentioning
confidence: 99%
“… Target/signaling Expansion effect Ref. Rapamycin mTOR 112 Garcinol/isogarcinol HATs 4.5-/7.4-fold HSCs 2.5-fold SRCs (garcinol) 118 TSA HDAC 2.5-fold CD34 + 40-fold CD34 + CD90 + 132 EchA ROS inhibition PI3K/AKT activation 1.33-fold CD34 + 1.7-fold CFUs 137 ASPP049 Hippo signaling ∼1.5-fold CD34 + CD38 − ∼2-fold hCD45 + 143 Chrysin p19, p57, MNDA, NR4A2, HOXB4 ∼1.5-fold HSCs 2.7-fold SRCs 145 Resveratol 1.84-fold CD34 + /CD133 + 138 , 139 , 140 CAPE HIF-1 α , SDF-1 α and VEGF-A 1.47-fold CFUs 1.77-fold SRCs 141 , 142 5-HT Apoptosis inhibition 1.73-fold CFU-F 12.2-fold CD34 + 146 α -Tocopherol ERK1/2 2-fold LSKs 147 ATRA RA receptor 4-fold CFUs 148 , 149 …”
Section: Small Molecules For Ex Vivo Hsc Expansionmentioning
confidence: 99%
“…18 ) also acts as an antioxidant, derived from propolis. 60 promoted ex vivo CB-HSCs expansion, homing and engraftment in vivo , mediated by up-regulation of HIF-1 α and vascular endothelial growth factor-A (VEGF-A) 141 , 142 .…”
Section: Small Molecules For Ex Vivo Hsc Expansionmentioning
confidence: 99%